Use of stabilometry and functional indicators to assess the risk of falls in elderly people in long stay institutions: Risk of falls in institutionalized older adults - Schlickmann, Ana Carolina Vieira; Kock, Kelser de Souza (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Introduction: The World Health Organization defines a fall as moving the body to a lower floor without sufficient time to correct this event. It involves the patient's risk factors and interrelated environmental factors. Stabilometry is a means of quantifying postural balance through electromagnetic sensors and specific modes. Objectives: To evaluate the risk of falling through stabilometry in institutionalized older adults. Methods: A cross-sectional study was carried out. The sample was made up of older adults living in a Long-Term Institution. Participants were evaluated using stabilometry with a Nintendo Wii Balance Board, mobility and functional balance Time Up and Go (TUG), and handgrip testing using a dynamometer. Results: The sample consisted of 35 participants with a median age of 74.0. The main comorbidities were hypertension and heart disease. The drugs used were diverse and were concentrated in a few groups. Twenty-eight participants were able to maintain themselves and perform all functional tests. Handgrip strength averaged 9kgf for women and 23kgf for men. The sample's average TUG time was 19.9 seconds. Functionality data was not associated with falls. Posturographic stabilometer data obtained a median of 101.9 cm for distance, 3.15 cm/s for speed, and 6.8 cm 2 for area. Advanced age and stabilometry speed were associated with falls were observed. Conclusion: Stabilometry data were good indicators for evaluating postural oscillations that may pre-exist a fall.